“Los juegos recreativos en el desarrollo del equilibrio motriz en niños y niñas de Educación Inicial” - Betancourt Fabara, Alejandra Liseth (2023)
The present investigation, "Recreational games in the development of motor balance in children of Initial Education," starts from the following problem about recreational games in the development of children of Initial Education. Teachers need to gain more knowledge about the topic addressed. It has been proposed as an objective to diagnose how recreational games affect the development of motor balance in children of the initial level. The qualitative approach was used; as an instrument, the thematic analysis method was used, which allows understanding of the process based on the inquiry and study of the information obtained; the research instruments applied were the question guide and observation sheet. It was determined that most of the interviewed teachers must consecutively maintain training to help the teaching-learning process with recreational games. Therefore, it is concluded that teachers need to acquire much new knowledge about how recreational games affect the development of motor balance. In this way, through different strategies, motor balance will improve in children.